2018
DOI: 10.11144/javeriana.uo37-79.aefr
|View full text |Cite
|
Sign up to set email alerts
|

Análisis estructural de la fibrina rica en plaquetas y sus aplicaciones en odontología regenerativa

Abstract: Antecedentes: La fibrina rica en plaquetas (PRF) es un concentrado plaquetario que se está usando con mayor frecuencia en medicina y odontología. Los resultados clínicos son variables posiblemente porque hay diferentes protocolos de obtención, equipos de centrifugado y técnicas de colocación. El desconocimiento de los aspectos estructurales puede afectar el resultado clínico. Objetivo: Describir  las características estructurales de la PRF en las diferentes zonas de la membrana. Métodos: Se realizó un estudio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…Figure 2 shows the structural characteristics and distribution of the PRF components. e histological analysis performed by Gutiérrez, et al (44) showed that there is no homogeneous platelet distribution throughout the FRP membrane. In the upper part, which is called platelet poor brin (PPF), there is a lower platelet concentration than in the lower BC (white blood cell layer) area.…”
Section: Platelet Rich Fibrin (Frp) or Fibrin Rich Plasma (Frp)mentioning
confidence: 99%
See 3 more Smart Citations
“…Figure 2 shows the structural characteristics and distribution of the PRF components. e histological analysis performed by Gutiérrez, et al (44) showed that there is no homogeneous platelet distribution throughout the FRP membrane. In the upper part, which is called platelet poor brin (PPF), there is a lower platelet concentration than in the lower BC (white blood cell layer) area.…”
Section: Platelet Rich Fibrin (Frp) or Fibrin Rich Plasma (Frp)mentioning
confidence: 99%
“…In the same study, scanning electron microscopy (SEM) analyses conrmed that the structure of the brin network and the cellular content are different in the three zones of the membrane, the concentration of platelets is higher in zone BC, and it is diminished in the PPF zone. Likewise, brin in zone BC is denser (29,33,36,44). PRF provides a temporary matrix for the injured tissue until remodeling is complete.…”
Section: Platelet Rich Fibrin (Frp) or Fibrin Rich Plasma (Frp)mentioning
confidence: 99%
See 2 more Smart Citations